The Effect of The PBL Model on Improving Critical Thinking Skills of V Grade Students in IPAS at SDN 122345 Pematangsiantar - Betsaida, Elisabeth; Thesalonika, Emelda; Pasaribu, Eva (Journal of Pedagogi, 2025)
This study aims to determine the effect of the Problem Based Learning (PBL) learning model on improving the critical thinking skills of fifth grade students in the science subject at SD Negeri 122345 Pematangsiantar. The research used a quantitative method with a One Group Pretest-Posttest design. The research sample was all 32 fifth-grade students. The research instrument was a descriptive test validated by experts. Data were collected through pretests and posttests, then analyzed using N-gain calculations. The results of the study showed an increase in the average value from 59.59% in the pretest to 94.19% in the posttest with an N-gain value of 0.86 which is included in the high category (≥0.7). This proves that the implementation of the Problem-Based Learning model has a significant impact on improving students' critical thinking skills in science learning. Therefore, PBL can be used as an effective alternative learning strategy to develop critical thinking skills and student engagement in elementary schools.